2018
DOI: 10.3329/imcjms.v12i1.35171
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of peptic ulcer by aqueous extract of Aegle marmelos leaf in rats

Abstract: Background and objectives: Aegle marmelos (Bael), a medicinal plant, has been widely used indigenously to treat many diseases in Bangladesh and other countries. The present study was carried out to evaluate the efficacy of A. marmelos leaf to prevent ethanol induced gastric ulcer in a rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Extensive experimental and clinical studies prove that Aegle marmelos possess various properties which helped to play a role in prevention and treatment of many diseases [29].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive experimental and clinical studies prove that Aegle marmelos possess various properties which helped to play a role in prevention and treatment of many diseases [29].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive experimental studies have demonstrated that A. marmelos may prevent ulcers and inflammation effectively. An aqueous extract of A. marmelos resulted in decreasing the ulcer score and ulcer index in rats’ stomachs, which was successfully achieved after the administration of 400 mg/kg of an aqueous extract from A. marmelos [ 57 ]. In other studies, ethanol, and an aqueous extract from A. marmelos , provided 56.33% and 37.2% protection of ulcers in vivo and the ethanol-induced gastric ulcer model, respectively, compared to standard drugs such as omeprazole (50.4% protection) (20 mg/kg body weight) [ 57 , 58 ].…”
Section: Plant Mediated Treatment Of Ulcer and Inflammatory Diseasesmentioning
confidence: 99%
“…An aqueous extract of A. marmelos resulted in decreasing the ulcer score and ulcer index in rats’ stomachs, which was successfully achieved after the administration of 400 mg/kg of an aqueous extract from A. marmelos [ 57 ]. In other studies, ethanol, and an aqueous extract from A. marmelos , provided 56.33% and 37.2% protection of ulcers in vivo and the ethanol-induced gastric ulcer model, respectively, compared to standard drugs such as omeprazole (50.4% protection) (20 mg/kg body weight) [ 57 , 58 ]. Ramakrishna et al investigated the effect of the oral administration of methanol extract from unripe A. marmelos in rats against H. pylori LPS-induced gastric ulcers which showed that this extract (500 mg/kg dose) caused a 93.98% reduction in the gastric ulcers [ 59 ].…”
Section: Plant Mediated Treatment Of Ulcer and Inflammatory Diseasesmentioning
confidence: 99%
“…They concluded that extracts of A. marmelos leaves have potential ability to prevent experimentally induced peptic ulcer formation. 38 Yarasi Gayathri et al (2015) evaluated the antioxidative and antiulcer effect of methanolic extract of unripe fruit of Aegle marmelos against Helicobacter pylori-Lipopolysaccharide induced gastric ulcer in Sprague Dawley rats. Volume of gastric juice, free and total acidity, acid output, pepsin concentration were analyzed and activities of enzymatic antioxidants, non-enzymatic antioxidants and the levels of lipid peroxidation products were also measured.…”
Section: Antibacterial Activity Of Aegle Marmelosmentioning
confidence: 99%